Investigating corruption a do-it-yourself guide - Coronel, Sheila S.; Tirol, Lorna Kalaw; Philippine Center for Investigative Journalism (Quezon City Philippine Center for Investigative Journalism, 2002)
A how-to manual for conducting your own investigation about corruption. Chapter arrangements and detailed instructions allow even first time users to navigate and understand the content showcasing the author's intent of educating even those with no prior background or understanding on how to expose corruption. Includes techniques for investigation sources of corruption, ways of measuring corruption, government structure and policy, and current efforts against corruption.
Keywords: Corruption investigation -- Philippines -- Handbooks, manuals etc; Government investigations -- Philippines -- Handbooks, manuals etc